IMPROVING THE ENVIRONMENTAL CARE POTENTIAL THROUGH SCIENCECOMIC (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The objectives of this article to provide a solution about one of the ways that can be done to increase the potential for loving the environment through the use of sciencomic. Indonesia is one of the regions that has been named as the world's lungs because 10% of the world's rainforests are located in Indonesian territory, but the fact shows that sixty-four million hectares of forests have been cleared over the past 50 years. Therefore, to overcome this, the need for planting an environmental care attitude early on. As the planting of environmental care for students, it is necessary to strengthen the concept of environmental care for students first. One of the ways to plant an effective concept is through sciencecomic in which there are interesting illustrations. The writing method uses literature studies on some relevant literature through library books, national and international journals. The literature search results show that based on Dale's Cone of Experience, sciencecomic utilization by displaying illustration images can help students understand and remember learning by 30%.